SISTEM INFORMASI PENEMPATAN PETUGAS JAGA KEAMANAN BERBASIS WEB STUDI KASUS DI SEKOLAH ACS JAKARTA - Fitria Rachmawati (Universitas Widyatama, 2021)
The insufficient information from irregular sources affirmatively brings about information invalidity, such as provided information during morning briefing and school events from manual log book of the security in the lobby also provides inadequate information. The rapid growing internet technology is able to support the application of information system regarding to work sift and record of security officer. The main objective of this study is to apply web-based information system of security shift work and school events. The writer applies literature study to accomplish this study regarding to the website work system, the design and website implementation. The conclusion obtained is that the information website is able to perform by using PHP, CSS and HTML code language combined with database of phpmyadmin. The information website takes the role as information provider that is useful for security officer to inform their work shift and school events for their workmate, parents of the students, staff and guests.